POSSIBLE ROLE OF SINGLE-VOXEL 1H MRS IN DIFFERENTIAL DIAGNOSIS OF SUPRASELLAR TUMORS - DR. A. EINSTIEN, M.D.,; DR. RAHUL A. VIRANI, M.D.,, (International Journal of Pharma and Bio Sciences, 2015)
Spatially resolved metabolic data obtained from 1H Spectroscopy provides information which increases the diagnostic accuracy of imaging sequences in predicting the histology of suprasellar neoplasms. The aim of the study was to evaluate the role of 1HMRS in various suprasellar neoplasms and to determine their spectral characteristics.60 cases were investigated with long-echo single voxel 1H -MRS using 1.5 Tesla clinical imager. Single-voxel spectroscopic examinations were guided by T1- weighted or T2-weighted images. We observed that whenever brain tissue was damaged or replaced by any process, NAA was markedly reduced. Extra-axial lesions, which do not infiltrate brain or which do not contain neuroglial tissue, didn’t demonstrate any NAA resonances. Cr was used as an internal standard for semi-quantitative evaluation of metabolic changes of other brain metabolites. Increased Cho was seen in processes with elevated cell-membrane turnover. Spectra obtained from different tumors exhibit reproducible differences, while histologically similar tumors yield characteristic spectra with only minor differences.